Meningkatkan Kesadaran Anak dalam Menerapkan Pola Hidup Sehat untuk Mencegah Virus Covid-19 - Prawiyogi, Anggy Giri; Suparman, Tarpan (Muttaqien Publishing Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR. KH.EZ. Muttaqien Purwakarta, 2024)
Real Work Lectures (KKN) are community service activities in certain areas or educational institutions. This KKN activity aims to provide real field work experience in the field of forming an independent and responsible attitude in carrying out work in the field. This KKN implementation was carried out online starting from July 1 2021 to July 31 2021 in North Pangulah Village, Kotabaru District. One of the individual work programs carried out by 17 students in North Pangulah Village was socialization regarding